Recovery and recycling of paper proceedings of the international symposium organised by the Concrete Technology Unit and held at the University of Dundee, Scotland, UK on 19 March 2001 - Dhir, Ravindra K.; Limbachiya, Mukesh C.; Newlands, Moray D. (Thomas Telford, 2001)
Vast quantities of used paper are discarded every day despite the technology existing to recover and recycle the material. Throughout the world, a number of legislative and industry-led initiatives, aimed at value recovery from paper collected for recycling, have been introduced with a view to increasing public awareness of paper recycling and creating a sustainable environment. This book presents the proceedings of an international Symposium organised by the Concrete Technology Unit, University of Dundee, whcih brings together some of the world's leading experts in the field of paper recovery and recycling.